Controlled synthesis of aligned Bi2S3 nanowires, sharp apex nanowires and nanobelts with its morphology dependent field emission investigations - Warule, Sambhaji S.; Chaudhari, Nilima S.; Kale, Bharat B.; Pandiraj, S.; Khare, Ruchita T.; More, Mahendra A. (Crystengcomm, 2013)
Well-aligned ultra-long Bi2S3 nanowire arrays with three kinds of apex morphology - abruptly sharpened apex, thin belt and flat - have been systematically fabricated on tungsten (W) foil by a facile hydrothermal method. The structural and morphological studies reveal formation of distinct tip morphologies, possessing high aspect ratio, single crystalline nature and growth along the orthorhombic [001] axis. A plausible growth mechanism has been proposed on the basis of observed experimental results. The field emission properties of Bi2S3 nanowires and sharp apex Bi2S3 nanowires are investigated. From the field emission studies, the values of the turn-on field, required to draw emission current density of similar to 0.1 mu A cm(-2), are observed to be similar to 2.01 and 1.21 V mu m(-1) for nanowires and sharp apex nanowires, respectively. Furthermore, ultra-long Bi2S3 nanowires are also grown on the W microtip (brush-like) from which very high emission current density similar to 11 mA cm(-2) has been drawn. These results are helpful for the design, fabrication and optimization of integrated field emitters using 1D nanostructures as cold cathode material.

Field emission properties of ZnO nanosheet arrays - Naik, Kusha Kumar; Khare, Ruchita T.; Chakravarty, Disha; More, Mahendra A.; Thapa, Ranjit; Late, Dattatray J.; Rout, Chandra Sekhar (Applied Physics Letters, 2014)
{Electron emission properties of electrodeposited ZnO nanosheet arrays grown on Indium tin oxide coated glass substrates have been studied. Influence of oxygen vacancies on electronic structures and field emission properties of ZnO nanosheets are investigated using density functional theory. The oxygen vacancies produce unshared d electrons which form an impurity energy state; this causes shifting of Fermi level towards the vacuum, and so the barrier energy for electron extraction reduces. The ZnO nanosheet arrays exhibit a low turn-on field of 2.4 V/mu m at 0.1 mu A/cm(2) and current density of 50.1 mu A/cm(2) at an applied field of 6.4 V/mu m with field enhancement factor

Metallic few-layer flowerlike VS2 nanosheets as field emitters - Rout, Chandra Sekhar; Khare, Ruchita T.; Kashid, Ranjit V.; Joag, Dilip S.; More, Mahendra A.; Lanzillo, Nicholas A.; Washington, Morris; Nayak, Saroj K.; Late, Dattatray J. (European Journal of Inorganic Chemistry, 2014)
We report first-principles DFT calculations of the single-layer VS2 work function, the experimental synthesis of flower-like few-layer-thick VS2 nanosheets by a simple one-step hydrothermal method, and the investigation of their field emission properties. The turn-on field required to draw emission current densities of 1 and 10 mu A/cm(2) were 4 and 5.01 V/mu m, respectively. The observed turn-on field values are attributed to the high field enhancement factor (ca. 2500), which is due to presence of sharp protrusions in the VS2 nanosheets. Furthermore, the field-emission current stability of the VS2 emitter shows stable behavior over a period of 12 h. Further, DFT calculations show that the work function (f) of the single-layer VS2 emitter is 6.01 eV.
Keywords: Density functional calculations; field emission; Layered compounds; Nanostructures; Sulfur; Vanadium

Pulsed laser-deposited MoS2 thin films on W and Si: field emission and photoresponse studies - Late, Dattatray J.; Shaikh, Parvez A.; Khare, Ruchita T.; Kashid, Ranjit V.; Chaudhary, Minakshi V.; More, Mahendra A.; Ogale, Satishchandra B. (ACS Applied Materials & Interfaces, 2014)
We report field electron emission investigations on pulsed laser-deposited molybdenum disulfide (MoS2) thin films on W-tip and Si substrates. In both cases, under the chosen growth conditions, the dry process of pulsed laser deposition (PLD) is seen to render a dense nanostructured morphology of MoS2, which is important for local electric field enhancement in field emission application. In the case of the MoS2 film on silicon (Si), the turn-on field required to draw an emission current density of 10 mu A/cm(2) is found to be 2.8 V/mu m. Interestingly, the MoS2 film on a tungsten (W) tip emitter delivers a large emission current density of similar to 30 mA/cm(2) at a relatively lower applied voltage of similar to 3.8 kV. Thus, the PLD-MoS2 can be utilized for various field emission-based applications. We also report our results of photodiode-like behavior in (n- and p- type) Si/PLDMoS2 heterostructures. Finally we show that MoS2 films deposited on flexible kapton substrate show a good photoresponse and recovery. Our investigations thus hold great promise for the development of PLD MoS2 films in application domains such as field emitters and heterostructures for novel nanoelectronic devices.
Keywords: field emission; MoS2; photodiode heterostructures; pulsed laser deposition; thin film

Enhanced electron field emission from NiCo2O4 nanosheet arrays - Naik, Kusha Kumar; Khare, Ruchita T.; Gelamo, Rogerio V.; More, Mahendra A.; Thapa, Ranjit; Late, Dattatray J.; Rout, Chandra Sekhar (Materials Research Express, 2015)
Electron emission properties of electrodeposited spinel NiCo2O4 nanosheet arrays grown on Ni foam have been studied. The work function of NiCo2O4 was calculated by density functional theory using the plane-wave basis set and used to estimate the field enhancement factor. The NiCo2O4 nanosheet arrays exhibited a low turn-on field of 1.86 V mu m(-1) at 1 mu A cm(-2) and current density of 686 mu A cm(-2) at 3.2 V mu m(-1), with field enhancement factor beta = 1460 and good field emission current stability. The field emission properties of the NiCo2O4 nanosheet arrays showed enhanced performance compared to chemically prepared NiCo2O4 nanosheets. Hence, the nanosheet arrays have great potential as robust high performance vertical structure electron emitters for future flat panel displays and vacuum electronic device applications.
Keywords: Density functional theory; field emission; nanosheets; NiCo2O4; spinel

Enhanced field emission of plasma treated multilayer graphene - Khare, Ruchita T.; Gelamo, Rogerio V.; More, Mahendra A.; Late, Dattatray J.; Rout, Chandra Sekhar (Applied Physics Letters, 2015)
Electron emission properties of multilayer graphene (MLG) prepared by a facile exfoliation technique have been studied. Effect of CO2 Ar, N-2, plasma treatment was studied using Raman spectroscopy and investigated for field emission based application. The CO2 plasma treated multilayer graphene shows an enhanced field emission behavior with a low turn on field of 0.18 V/mu m and high emission current density of 1.89 mA/cm(2) at an applied field of 0.35 V/mu m. Further the plasma treated MLG exhibits excellent current stability at a lower and higher emission current value. (C) 2015 AIP Publishing LLC.

Field emission properties of spinel ZnCo2O4 microflowers - Ratha, Satyajit; Khare, Ruchita T.; More, Mahendra A.; Thapa, Ranjit; Late, Dattatray J.; Rout, Chandra Sekhar (RSC Advances, 2015)
ZnCo2O4 microflowers were synthesized by a simple low temperature hydrothermal route. A single three-dimensional microflower consists of hundreds of self-assembled petals, with a thickness of several nanometers. These microflowers have exceptionally thin edges with a few petal layers. The ZnCo2O4 microflowers appeared to be stable and good field emitters.

Graphene nanoribbons as prospective field emitter - Khare, Ruchita T.; Shinde, Dhanraj B.; Bansode, Sanjeewani; More, Mahendra A.; Majumder, Mainak; Pillai, Vijayamohanan K.; Late, Dattatray J. (Applied Physics Letters, 2015)
Field emission characteristics of graphene nanoribbons (GNRs) synthesized by unzipping of multiwall carbon nanotubes using a facile hydrothermal route have been investigated at a base pressure of 1 x 10(-8) mbar. The values of turn-on field, required to draw an emission current densities of 1 and 10 mu A/cm(2), are found to be 2.8 and 5.8 V/mu m, respectively, and a maximum emission current density of 500 mu A/cm(2) has been drawn at an applied field of 9.8 V/mu m. The emission current stability of the GNRs emitter was studied at preset values of 1 and 10 mu A over a period of 3 h, and is found to be excellent. The field emission results demonstrated herein suggest that GNRs based field emitters can open up many opportunities for their potential utilization as large area field emitters in various vacuum micro-nanoelectronic devices such as flexible field emission displays, portable X-ray, and microwave tubes. (C) 2015 AIP Publishing LLC.

One-pot thermal evaporation synthesis of CdS-RGO hetrostructure and its field emission study - Bansode, Sanjeewani R.; Khare, Ruchita T.; More, Mahendra A.; Late, Dattatray J. (2015 28TH International Vacuum Nanoelectronics Conference (IVNC), 2015)
CdS-RGO heterostructure was synthesized by thermal evaporation method. The as-synthesized CdS-RGO heterostructure was characterized using X-ray Diffraction, SEM, and EADX, before field emission (FE) studies. The FE characteristics of a planar emitter made up of as-synthesized CdS-RGO heterostructures were measured at the base pressure 1x10(-8) mbar. The synthesized CdS-RGO heterostructure emitter is found to deliver a current density similar to 70 mu A/cm(2) at an applied electric field of similar to 4.7 V/mu m. Moreover, the nanocomposite shows excellent emission stability without significant current degradation making CdS-RGO heterostructure as a promising electron source for practical applications in various vacuum nano-microelectronic devices.

Transition metal di-chalcogenides and their nanocomposite prospective field emitters - Khare, Ruchita T.; More, Mahendra A.; Late, Dattatray J. (2015 28TH International Vacuum Nanoelectronics Conference (IVNC), 2015)
Layered structured transition metal di-chalcogenides has attracted researchers as a substitute of graphene and its forms for various applications. In an attempt to explore field emission properties of these graphene analogues, synthesis and field emission behaviour of a few layered transition metal di-chalcogenides (TMDs) VS2, MoS2, MoO3 have been investigated at a base pressure of 1x 10(-8) mbar. Furthermore, to improve the field emission properties, composites with RGO and respective oxides were synthesized and compared with the pristine ones. The TMDs and their composites is synthesized employing hydrothermal synthesis route. The preliminary results show that these TMD's and their composites, when synthesized in a controlled manner, can serve as potential field emitters for future field emission based devices.

Glucose sensing and low-threshold field emission from MnCo2O4 nanosheets - Naik, Kusha Kumar; Khare, Ruchita T.; More, Mahendra A.; Late, Dattatray J.; Rout, Chandra Sekhar (RSC Advances, 2016)
Manganese cobalt oxide (MnCo2O4) nanosheets were grown on nickel (Ni) foam by a simple electrodeposition method. The as-synthesized nanosheets were characterized using X-ray diffraction and scanning electron microscopy. The Ni foam supports the growth of MnCo2O4 nanosheets without any aggregation, thereby increasing its catalytic and electronic properties. The electrochemical studies show that MnCo2O4 exhibits excellent electrocatalytic activity towards glucose sensing applications. The MnCo2O4 based glucose sensor shows a good sensitivity value of 8.2 mA mM(-1) cm(-2), with a response time of 19 s. In addition to this, field emission studies of as-synthesized MnCo2O4 reveal a low turn-on field value of 1.9 V mm(-1) and good emission current stability, demonstrating MnCo2O4 nanosheets as a good field emitter material.

Promising field electron emission performance of vertically aligned one dimensional (1D) brookite (beta) TiO2 nanorods - Devan, Rupesh S.; Ma, Yuan-Ron; More, Mahendra A.; Khare, Ruchita T.; Antad, Vivek V.; Patil, Ranjit A.; Thakare, Vishal P.; Dhayal, Rajendra S.; Schmidt-Mende, Lukas (RSC Advances, 2016)
We evidence field-electron emission (FE) studies on the large-area array of one-dimensional (1D) brookite (beta) TiO2 nanorods. The pure 1D beta-TiO2 nanorods of 10 nm width and 760 nm long were synthesized on Si substrate utilizing hot-filament metal vapor deposition technique. X-ray diffraction (XRD) and transmission electron microscopy (TEM) analysis evidenced the beta-TiO2 nanorods to be composed of orthorhombic crystals in brookite (beta) phase. X-ray photoemission spectroscopy (XPS) revealed the formation of pure stoichiometric (i.e. 1 : 1.98) 1D TiO2 nanorods. The values of turn-on field, required to draw current density of 10 mA cm(-2), was observed 3.9 V mu m(-1) for pristine 1D beta-TiO2 nanorods emitters, which were found significantly lower than doped/undoped 1D TiO2 nanostructures (i.e. nanotubes, nanowires, nanorods) based field emitters. The enhanced FE behavior of the TiO2/Si emitter can be attributed to modulation of electronic properties due to the high aspect ratio of vertically aligned TiO2 nanorods. Furthermore, the orthodox emission situation of pristine TiO2/Si emitters exhibit good emission stability and reveal their potentials as promising FE material.

Nano-heteroarchitectures of two-dimensional MoS 2 @ one-dimensional brookite TiO 2 nanorods: prominent electron emitters for displays - Devan, Rupesh S.; Thakare, Vishal P.; Antad, Vivek V.; Chikate, Parameshwar R.; Khare, Ruchita T.; More, Mahendra; Dhayal, Rajendra S.; Patil, Shankar I.; Ma, Yuan-Ron; Schmidt-Mende, Lukas (ACS Omega, 2017)
We report comparative field electron emission (FE) studies on a large-area array of two-dimensional MoS2-coated @ one-dimensional (1D) brookite (β) TiO2 nanorods synthesized on Si substrate utilizing hot-filament metal vapor deposition technique and pulsed laser deposition method, independently. The 10 nm wide and 760 nm long 1D β-TiO2 nanorods were coated with MoS2 layers of thickness ∼4 (±2), 20 (±3), and 40 (±3) nm. The turn-on field (Eon) of 2.5 V/μm required to a draw current density of 10 μA/cm² observed for MoS2-coated 1D β-TiO2 nanorods emitters is significantly lower than that of doped/undoped 1D TiO2 nanostructures, pristine MoS2 sheets, MoS2@SnO2, and TiO2@MoS2 heterostructure-based field emitters. The orthodoxy test confirms the viability of the field emission measurements, specifically field enhancement factor (βFE) of the MoS2@TiO2/Si emitters. The enhanced FE behavior of the MoS2@TiO2/Si emitter can be attributed to the modulation of the electronic properties due to heterostructure and interface effects, in addition to the high aspect ratio of the vertically aligned TiO2 nanorods. Furthermore, these MoS2@TiO2/Si emitters exhibit better emission stability. The results obtained herein suggest that the heteroarchitecture of MoS2@β-TiO2 nanorods holds the potential for their applications in FE-based nanoelectronic devices such as displays and electron sources. Moreover, the strategy employed here to enhance the FE behavior via rational design of heteroarchitecture structure can be further extended to improve other functionalities of various nanomaterials.

Titanium trisulfide nanosheets and nanoribbons for field emission- based nanodevices - Pawbake, Amit S.; Khare, Ruchita T.; Island, Joshua O.; Flores, Eduardo; Ares, Jose R.; Sanchez, Carlos; Ferrer, Isabel J.; Pawar, Mahendra; Frank, Otakar; More, Mahendra A.; van der Zant, Herre S. J.; Castellanos-Gomez, Andres; et al. (ACS Applied Nano Materials, 2023)
The field emission (FE) properties of TiS3 nanosheets and nanoribbons, synthesized by direct sulfuration of bulk titanium, are investigated. The nanosheets show an enhanced FE behavior with a low turn-on field of similar to 0.3 V/ mu m, required for drawing an emission current density of similar to 10 mu A/cm2. Interestingly, the TiS3 nanosheet emitter delivered a large emission current density of similar to 0.9 mA/ cm2 at a relatively low applied electric field of similar to 0.4 V/mu m. We have estimated the values of the field enhancement factor (beta), which are found to be similar to 5 x 104 for the TiS3 nanosheet emitter and similar to 4 x 103 for the nanoribbon emitter. We attribute the superior FE performance to the presence of atomically sharp edges and the reduced thickness of TiS3, as reflected in the high value of beta. In fact, the nanosheet sample presents a higher density of ultrathin layers (similar to 12 nm-thick), and thus, they have a larger edge to volume ratio than the nanoribbon samples (which are similar to 19 nm-thick). The superior FE behavior of TiS3 nanosheets over nanoribbons makes them a propitious field emitter and can be utilized for various FE-based applications, demanding large emission currents and lower operational voltages. Moreover, the FE current stability recorded on these samples confirms their promising performance. Thus, the present investigation brings out a great promise of TiS3 nanosheets and nanoribbons as field emitters for vacuum nanoelectronics devices.
Keywords: Current stability; field emission; nanoribbon; nanosheets; TiS3